Localization of Sustainable Development Goals in Nepal - Ghimire, Bidhya Jyoti (Rural Development Journal, 2025)
This study investigates Nepal's efforts to localize Sustainable Development Goals (SDGs) within the framework of its governance system, emphasizing the role of local and regional governments in achieving global sustainability targets. The research employs mixed methods, combining secondary data from government reports, academic studies, and international organizations to analyze progress, challenges, and strategies. Key findings highlight Nepal's integration of SDGs into national policies and localized development plans, demonstrating progress in poverty reduction, gender equality, and infrastructure development. However, challenges such as financial constraints, research and data gaps, as well as coordination issues prevail, intensified by the COVID-19 pandemic. The study emphasizes the significance of inclusive governance, community participation, and targeted interventions to address disparities and ensure sustainable growth. By aligning local priorities with global goals, Nepal's experience offers understanding of effective SDG localization in developing countries.